Rapid deployment versus conventional bioprosthetic valve replacement for aortic stenosis - Ensminger, Stephan; Bekeredjian, Raffi; Katus, Hugo (Journal of the American College of Cardiology, 2018)
Background - Surgical aortic valve replacement using conventional biological valves (CBVs) is the standard of care for treatment of old patients with aortic valve disease. Recently, rapid deployment valves (RDVs) have been introduced. - Objectives - The purpose of this study was to report the nationwide German experience concerning RDVs for treatment of aortic valve stenosis and provide a head-to-head comparison with CBVs. - Methods - A total of 22,062 patients who underwent isolated surgical aortic valve replacement using CBV or RDV between 2011 and 2015 were enrolled into the German Aortic Valve Registry. Baseline, procedural, and in-hospital outcome parameters were analyzed for CBVs and RDVs using 1:1 propensity score matching. Furthermore, 3 RDVs were compared with each other. - Results - A total of 20,937 patients received a CBV, whereas 1,125 patients were treated with an RDV. Patients treated with an RDV presented with significantly reduced procedure (160 min [25th to 75th percentile: 135 to 195 min] vs. 150 min [25th to 75th percentile: 127 to 179 min]; p < 0.001), cardiopulmonary bypass (83 min [25th to 75th percentile: 68 to 104 min] vs. 70 min [25th to 75th percentile: 56 to 87 min]; p < 0.001), and aortic cross clamp times (60 min [25th to 75th percentile: 48 to 75 min] vs. 44 min [25th to 75th percentile: 35 to 57 min]; p < 0.001), but showed significantly elevated rates of pacemaker implantation (3.7% vs. 8.8%; p < 0.001) and disabling stroke (0.9% vs. 2.2%; p < 0.001), whereas in-hospital mortality was similar (1.7% vs. 2.2%; p = 0.22). These findings persisted after 1:1 propensity score matching. Comparison of the 3 RDVs revealed statistically nonsignificant different pacemaker rates and significantly different post-operative transvalvular gradients. - Conclusions - In this large, all-comers database, the incidence of pacemaker implantation and disabling stroke was higher with RDVs, whereas no beneficial effect on in-hospital mortality was seen. The 3 RDVs presented different complication profiles with regard to pacemaker implantation and transvalvular gradients. (German Aortic Valve Registry [GARY]; NCT01165827)
Gesehen am 18.02.2020